HEDOLE DOLE : STUNTING TRADISIONAL MASYARAKAT WAKATOBI - Sumiman Udu; Laode Anhusadar; Alias Alias; La Ali (Institut Agama Islam Negeri Kendari, 2019)
Every civilization has knowledge about health. From the beginning until now the most vulnerable groups in terms of health are toddlers and pregnant women. In the Wakatobi community, the health of children or toddlers is also an important aspect that is a priority of the local government to improve the quality of children's lives. In an effort to improve the quality of life for toddlers, the Wakatobi community has a culture as a traditional stunting that has been growing and developing in the community. This study used an ethnographic approach, so the data collection of data analysis uses ethnographic principles. This approach was expected to reveal how the Wakatobi community views health and quality of life for toddlers. The results of this study indicated that the Wakatobi community has had a traditional earrings concept called the Hedole Dole. Through the Hedole Dole ritual, toddlers have special treatment from a sando or traditional birth attendant. After experiencing the Dole Dole ritual, Wakatobi children possessed strong endurance. They will have strong endurance to fight various weather changes. Wakatobi believes and believes that this tradition has improved the quality of life and endurance of their toddlers. They also assume that healthy children are children who have a healthy body and mind. Wakatobi people think that through the ritual tradition of Dole Dole food can have a strong immune system. The process of their idols will be given various types of herbs and treatments that make their bodies stronger and resistant to various diseases.